Evolution of the microbiota of wound infections in military personnel during the full-scale russian invasion: a retrospective cohort study (2022–2024) - N.A. Beley; O.A. Loskutov; A.M. Strokan; O.B. Izmaylova (Медицина неотложных состояний)
Background. Infectious complications remain one of the main causes of mortality and morbidity in blast injury among military personnel. The prevalence of infectious complications in blast injury reaches 35 %, and often the causative agents of such infections are multidrug-resistant microorganisms. The purpose was to analyze the dynamics of causative agents of wound infections in military personnel during the full-scale russian invasion. Materials and methods. We conducted a retrospective cohort study of servicemen who were injured during hostilities and were treated at the Feofaniya Clinical Hospital from March 2022 to March 2024. Wound culture was mandatory for study inclusion. Samples were taken from wounds with signs of inflammation, and microbiological testing was carried out in the laboratory of Feofaniya Clinical Hospital. Cultures were conducted in accordance with standard methods of medical microbiology. The disc diffusion method was used to determine the sensitivity of isolates to antimicrobial drugs. Results. The study included 478 servicemen (mean age of 36.60 ± 0.42 years, range 18–67, 99.6 % were males) who have had 1441 wound cultures, and 2483 isolates were identified. No pathogen was detected in 289 cases (11.63 %), fungal isolates were detected in 59 (2.38 %) cases, and the remaining isolates (2135; 85.98 %) were found to be bacterial. Gram-negative flora predominated among them — 80.2 % (95% confidence interval (CI) 78.4–81.8), while Gram-positive flora accounted for 19.8 % (95% CI 18.2–21.6), p < 0.001. The most common pathogens were Klebsiella pneumoniae (22.8 %; 95% CI 21.2–24.5), Acinetobacter baumannii (20 %; 95% CI 18.5–21.6), Pseudomonas aeruginosa (13.6 %; 95% CI 12.3–14.9) and Enterococcus spp. (6.2 %; 95% CI 5.3–7.2). Other pathogens were observed with a proportion of < 5 %. Monomicrobial cultures accounted for 50.5 % (95% CI 47.8–53.3), two isolates were found in 34.0 % (95% CI 31.4–36.6), three isolates — in 12.7 % (95% CI 10.9–14.5), four isolates — in 2.2 % (95% CI 1.4–3.0) and five isolates — in 0.6 % (95% CI 0.3–1.1) of all cultures. There was a significant level of antibiotic resistance — 99.7 % of Klebsiella pneumoniae isolates were multidrug-resistant. Conclusions. Wound infection in blast injury is characterized by a significant predominance of Gram-negative microflora with a high prevalence of antibiotic resistance. Polymicrobial flora was identified in half of the cases of wound infection.